Review of The Persian Translation of Heidegger and Christianity - Maryam Soltani Kouhestani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper reviews the Persian translation of Heidegger and Christianity, by John Macquarrie’s Lectures from 1993-1994 at the University of Oxford, published in 1994 by the Continuum Publishing Company, New York and in Iran in 1397, with the Persian translation of Shahabeddin Abbasi by the Parseh book Publishing Company. In this review, after introducing the book and introducing the formal and content of the work, the critique of three of the world’s leading scholars on Heidegger and Christianity has been examined, and then the points and defects of the work have been examined formally and content. The concluding summary of the present article suggests that the Persian translation, regardless of the instances where the need to be reviewed, due to clear translation, understandable, observance of scholarly trust, text abstraction from print mistakes and the maximum accuracy in choosing Persian equivalents for Heidegger’s terms, it is useful for Iranian readers to become acquainted with Macquarrie’s understanding of Heidegger’s relationship with Christianity. But, as some critics of Heidegger and Christianity have pointed out, in spite of Macquarrie’s attempt to explain Heidegger’s relationship with Christianity, this book does not provide a clear view of the relationship Heidegger with Christianity to the reader.